Regionalismo e Sociedade Política (GEOgraphia, 2009)
Resumo Regionalismo e Nacionalismo são forças transformadoras da paisagem política no final do século XX. Como todos nós sabemos, elas têm um alto potencial de destruição. Porque a geografia humana tradicional – como ciência do regional – tem tão pouco potencial explicativo para estes proces-sos? Forneço aqui algumas respostas a esta questão e sugiro – a partir da filosofia social de Alfred Schutz – uma perspectiva geográfica do mundo, proporcionando à geografia social uma maior capacidade de resolver problemas na modernidade tardia. Palavras-chave: regionalismo – globalização – espaço – teoria da ação.Abstract Regionalism and Nationalism are transformative forces of the political landscape at the end of the 20th century. As we all know, they have a high potential of destruction. Why has traditional human geography – as the science of the regional – so little explanatory potential when looking at these social processes? In this paper, I will give some answers to this question and suggest – drawing from the social philosophy of Alfred Schutz – a geographical perspective of the world, giving to social geography a higher capacity of problem-solving in the age of late-modernity. Keywords: regionalism – globalization – space – action theory